Effective expansion of umbilical cord blood hematopoietic stem/progenitor cells by regulation of microencapsulated osteoblasts under hypoxic condition. - Song, K; Zhao, G; Liu, T; Zhang, L; Ma, X; Liu, J; Cui, Z (2009)
The expansion of hematopoietic stem/progenitor cells (HSPCs) from umbilical cord blood (UCB) with the support of microencapsulated osteoblasts under hypoxia environment was investigated. The expansion of HSPCs was evaluated through the total number of UCB mononuclear cells (MNCs) produced, their repopulating potential with the colony-forming unit assay (CFU-Cs) and CD34(+) phenotypic analysis with flow cytometry. At the end of 7 days of culture, the UCB-MNCs, CFU-Cs and CD34(+) cells had achieved 18.7 +/- 1.6, 11.6 +/- 0.9 and 23.4 +/- 2-fold expansions, respectively, in the test groups. These were significantly different from those in control groups. Microencapsulated osteoblasts under hypoxia conditions had therefore a significant effect on the expansion potential of HSPCs in vitro.